INTRINSIC MOTIVATION OF SANTRI IN THE TAHFIDZUL QUR'AN PROGRAM AT PONDOK DARUT TAUHID PESANTREN ZAINUL HASAN GENGGONG PAJARAKAN - Rizqiyatul Firdausiah, Himami; Aziz Wahab, Abd.; Fatimah, Nur (Qawwam : The Leader's Writing, 2025)
This study aims to examine the intrinsic motivation of students in participating in the Tahfidzul Qur'an program at the Pondok Darut Tauhid Pesantren Zainul Hasan Genggong. The main focus of the study is how internal motivation such as love for the Qur'an, the desire to gain Allah's pleasure, and the spirit of achieving personal achievement play a role in the success of the tahfidz program. The approach used is a qualitative approach with a case study method. Data were obtained through in-depth interviews, participatory observation, and documentation of students who are active in the tahfidz program. Data analysis was carried out descriptively through data reduction, data presentation, and drawing meaning from field findings. The results of the study indicate that intrinsic motivation of students has a significant role in the sustainability and achievement of memorizing the Qur'an. Students who have strong internal motivation tend to be more consistent, disciplined, and have higher resilience in facing challenges during the memorization process. In addition, the supportive pesantren environment and the role of ustadz in providing spiritual guidance also strengthen this motivation. This finding provides an illustration that the success of the tahfidz program is not only determined by the teaching method, but is also greatly influenced by the strength of motivation from within the students themselves.